A wide-bandgap π-conjugated polymer for high-performance ternary organic solar cells with an efficiency of 17.40%. (November 2021) - Gokulnath, Thavamani; Choi, Jungmin; Park, Ho-Yeol; Sung, Kyungmin; Do, Yeongju; Park, Hyungjin; Kim, Junyoung; Reddy, Saripally Sudhaker; Kim, Jehan; Song, Myungkwan; Yoon, Jinhwan; Jin, Sung-Ho
Abstract: Although substantial progress has been made at increasing power conversion efficiencies (PCEs) the field of ternary organic solar cells (TOSCs) during the past few years, choice of π-conjugated polymers that exhibit strong complementary spectra and achieve high photovoltaic parameters (open-circuit voltage ( V oc), short-circuit current density ( J sc), fill factor (FF), and PCE) simultaneously is limited. In this paper, TOSCs demonstrated a high PCE of 17.09% based on a π-conjugated polymer (named SiCl-BDT, bandgap ≈ 1.84 eV) as a third component (15 wt%) to the host binary system consisting of a PM7:Y7. The third component was used to achieve enhanced absorption coefficient (λmax = 5.5 × 10 4 cm −1 ) and more balanced charge carrier transport, frontier molecular orbital (FMO) energy levels, and blend miscibility, contributed to an improved FF of 70.38% and yielded an impressive J sc of 27.37 mA/cm 2 and V oc of 0.84 V. The PCE was higher than the host PM7:Y7 (15.13%) binary device. In addition, we found the photovoltaic performance of TOSCs could be further increased to a benchmark PCE of 17.40% using an interface engineering strategy. Thus, enables efficient charge transfer in TOSCs compared with that of without interlayer TOSCs, leading to high J sc, V oc. The resulting encapsulation-free TOSCs showed excellent ambient and thermal stability. Accordingly, this work suggests that the use of a passivated electron transporting layer (ETL) and a π-conjugated polymer as a third component offers a promising means of overcoming the lower PCEs of OSCs. Graphical Abstract: ga1 Highlights: The devices were fabricated in binary and ternary organic solar cells (TOSCs). The cascade LUMO alignment and complementary absorption improve the performance of TOSCs. The PCE of SiCl-BDT incorporated with binary host device (PM7:Y7) TOSCs reached to 15.12%, 17.09%. An improved efficiency of 17.40% was achieved in a TOSC device using 3-(1-pyridinio)-1-propanesulfonate as a ZnO-passivation layer. PM7:SiCl-BDT:Y7 based devices exhibit good thermal and ambient stability.